Faktor- Faktor yang Mempengaruhi Kelemahan Sistem Pengendalian Internal pada Pemerintah Daerah Kabupaten/Kota di Sumatera Barat - Kintana Hawari; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the factors that influence the weakness of the internal control system in the West Sumatra Regency/City local government in 2018-2021. The data in this study uses secondary data that is obtained from the report on the results of the examination of the local government financial statements (LKPD) and supported by the summary of the results of the semester examination (IHPS) and the balance sheet report from the Supreme Audit Agency of West Sumatra, then the report on the human development index, the SKPD report from the Central Statistics Agency of West Sumatra. The sampling technique in this study used a purposive sampling method that produced a total sample of 19 districts/cities with a period of 4 years. Data analysis used multiple linear regression analysis. The results of this study indicate that the quality of human resources, complexity, and size has no significant effect on internal control weakness. The limitation of this research is that it only focuses on the District/City of West Sumatra Province. This means that the results of the research might be different if it were carried out in other regions, considering the different characteristics of each region in Indonesia. This research was only conducted for 4 budget years, namely 2018 to 2021.